Perkembangan Digital Marketing Online sebagai Metode Alternatif Produk Wirausaha Mahasiswa Akademi Keuangan Perbankan Nusantara (Sebuah Analisis Perspektif Syariah Islam) - Ismail; Irma Suryani (Jurnal EMT KITA, 2022)
The purpose of this study is to find out the development of online digital marketing by using alternatives to take advantage of the search for the social networking market through the latest provided applications for the sale of business products for the students of the Akademi Keuangan Perbankan (AKUBANK) Nusantara Aceh Timur in the current millennial era. The research was conducted on the efforts of AKUBANK Nusantara students in East Aceh using qualitative research methods, namely matching existing theories with empirical reality using descriptive methods to find out in-depth how the development of online digital marketing is carried out by Akubank Nusantara Aceh Timur students. Data collection in this study was carried out by interviewing business owners, participatory observation methods, and also through documentation methods. The results of this study indicate that students, experiencing an increase from the average business they run, have increased from day to day due to affordable prices, the quality of their products in front of trying alternative methods by utilizing the search for social networking market through the latest provided applications. This is a good sign for the marketing of Akubank Nusantara students in East Aceh itself. After analyzing the suitability of existing theories and rules with practice in the field, it can be concluded that the application of online digital marketing to the businesses of Akubank Nusantara Aceh Timur students is in accordance with sharia marketing.